Fear effects associated with predator presence and habitat structure interact to alter herbivory on coral reefs - Fraser Januchowski-Hartley (Biology Letters, 2019)
Foraging decisions made by consumers are driven by a range of factors, including non-consumptive predation effects. These effects are often mediated by both the presence or absence of predators, and the structure of the surrounding habitat that may visually occlude prey, thus increasing the predation risk. Under such circumstances, it is likely that prey will be warier, and this will be reflected in their rates of browsing. We used models of the predatory coral reef fish Plectropomus leopardus and experimentally manipulated the density of the macroalga Sargassum ilicifolium to investigate how these factors interact on a coral reef in Singapore. We found that the interaction between predator- and habitat associated fear effects influence the rate of herbivory, with declining rates with increasing macroalgal density, likely due to visual occlusion by macroalgae making it more difficult to detect predators, and thus increasing wariness in browsers. The predator model appeared to have an impact on browsing, but only at low-densities of Sargassum. Our results suggest that when fishes' knowledge of their surroundings is less certain, they will respond with a heightened wariness, regardless of acute predation cues.